2013
DOI: 10.1111/eth.12137
|View full text |Cite
|
Sign up to set email alerts
|

On the Validity of a Single (Boldness) Assay in Personality Research

Abstract: A common method to assess behavioral types in personality research involves the use of a single emergence test (employed by researchers working on fish, avian, mammal, amphibian, and invertebrate taxa), whereby a shorter latency to emerge from a holding container into a novel environment is inferred to represent greater ‘boldness’. Although any behavior might be context specific, studies using this single assay type must assume it reflects boldness in other similar contexts, otherwise it cannot reflect persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 60 publications
7
99
1
Order By: Relevance
“…Although consistent with results from a study of FID in semiferal Welsh Mountain ponies (Birke et al 2011), this result is nonetheless surprising given that short-term desensitization has been documented for a number of behavioural assays (e.g., Bell et al 2009;Beckmann and Biro 2013) and is widely assumed to occur for FID (Rodríguez-Prieto et al 2009). In contrast, there are two lines of evidence for long-term habituation to people.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although consistent with results from a study of FID in semiferal Welsh Mountain ponies (Birke et al 2011), this result is nonetheless surprising given that short-term desensitization has been documented for a number of behavioural assays (e.g., Bell et al 2009;Beckmann and Biro 2013) and is widely assumed to occur for FID (Rodríguez-Prieto et al 2009). In contrast, there are two lines of evidence for long-term habituation to people.…”
Section: Discussionsupporting
confidence: 76%
“…We aimed to determine if FID is a repeatable trait with the potential to form the basis of future research on the evolution and maintenance of risk aversion and island tameness. Because animals are known to habituate (become desensitized) to behavioural assays (e.g., Beckmann and Biro 2013) and generally assumed to occur for FID (Rodríguez-Prieto et al 2009), we tested if FID decreased over successive measurements made on the same day or on successive days. In addition, because risk-taking can vary between the sexes (Samia et al 2015), we tested if FID varied between males and females.…”
Section: Introductionmentioning
confidence: 99%
“…The study of animal personalities generally seeks to understand how and why individuals maintain personalities, as well as their ecological and evolutionary implications [33,55]. We have shown that the probability of reaching consensus in a patchy environment does not vary between groups and is independent of the distributions of personalities within groups.…”
Section: (B) Group Personalitymentioning
confidence: 92%
“…construct validity; Carter et al, 2013, Koski, 2014, researchers must also consider whether the design of the test and the behaviours measured are ecologically relevant for the species of interest (i.e. ecological validity; Réale et al, 2007;Beckmann and Biro, 2013;Koski, 2014). This is especially true when trying to understand the life-history implications or fitness outcomes associated with a particular behaviour and when comparing studies.…”
Section: How Should We Quantify Animal Personality? Selecting the Rigmentioning
confidence: 99%